Abstracting practices in libraries (Anmol Pubications, 2001)
Contents of material: 1/ Introduction. 2/ Abstracting practies. 3/ Periodicals listing and accessioning. 4/ Online computer service. 5/ Bibliographic display. 6/ Bibliographic control. 7/ Functions of abstracting. 8/ Acquisition system. 9/ Interlibrary lending.10/ Future abstracting practices.